Qualitative risk assessment of HPAI H5N1 transmission between small-scale commercial broiler chicken farms in Bogor, Indonesia - Idris, S.; Palupi, M.F.; Sudiana, E.; Unger, Fred (International Food Policy Research Institute, 2010)
As part of the DFID-funded Pro-Poor HPAI Risk Reduction Project, a qualitative risk assessment was conducted for risk questions agreed during a stakeholder workshop in November, 2008, related to transmission of HPAI H5N1 between small-scale commercial broiler farms in the District and Municipality of Bogor.